Green tea ingestion greatly reduces plasma concentrations of nadolol in healthy subjects - Misaka, S.; Yatabe, J.; Müller, Fabian; Takano, K.; Kawabe, K.; Gläser, Hartmut; Yatabe, M. S.; Onoue, S.; Werba, J. P.; Watanabe, H.; Yamada, S.; Fromm, Martin; et al. (Clinical Pharmacology & Therapeutics, 2014)
This study aimed to evaluate the effects of green tea on the pharmacokinetics and pharmacodynamics of the ?-blocker nadolol. Ten healthy volunteers received a single oral dose of 30 mg nadolol with green tea or water after repeated consumption of green tea (700 ml/day) or water for 14 days. Catechin concentrations in green tea and plasma were determined. Green tea markedly decreased the maximum plasma concentration (Cmax) and area under the plasma concentration-time curve (AUC0-48) of nadolol by 85.3% and 85.0%, respectively (P < 0.01), without altering renal clearance of nadolol. The effects of nadolol on systolic blood pressure were significantly reduced by green tea. [(3)H]-Nadolol uptake assays in human embryonic kidney 293 cells stably expressing the organic anion-transporting polypeptides OATP1A2 and OATP2B1 revealed that nadolol is a substrate of OATP1A2 (Michaelis constant (Km) = 84.3 ?mol/l) but not of OATP2B1. Moreover, green tea significantly inhibited OATP1A2-mediated nadolol uptake (half-maximal inhibitory concentration, IC50 = 1.36%). These results suggest that green tea reduces plasma concentrations of nadolol possibly in part by inhibition of OATP1A2-mediated uptake of nadolol in the intestine.
EVALuna2:8680